Peroxisome Proliferator-Activated Receptor Activation in Precision-Cut Bovine Liver Slices Reveals Novel Putative PPAR Targets in Periparturient Dairy Cows - Busato, Sebastiano; Ford, Hunter R.; Abdelatty, Alzahraa M.; Estill, Charles T.; Bionaz, Massimo (Frontiers in Veterinary Science, 2022)
Metabolic challenges experienced by dairy cows during the transition between pregnancy and lactation (known as peripartum) are of considerable interest from a nutrigenomic perspective. The mobilization of large amounts of non-esterified fatty acids (NEFA) leads to an increase in NEFA uptake in the liver, which can cause hepatic lipid accumulation. Peripartum NEFA activate the Peroxisome Proliferator-activated Receptor (PPAR), a transcriptional regulator with known nutrigenomic properties. Despite the importance of the topic, current in vitro models of the bovine liver are inadequate, as the isolation of primary hepatocytes is resource intensive, and the resulting cells lose their characteristic phenotype within hours. The objective of the current study was to evaluate the use of precision-cut liver slices (PCLS) from liver biopsies as a model for PPAR activation in periparturient dairy cows. Three primiparous Jersey cows were enrolled in the experiment, and PCLS from each were prepared prepartum (-8.0±3.6 DIM) and postpartum (+7.7±1.2 DIM), and treated independently with PPAR modulators: for PPARα (agonist WY-14643 , antagonist GW-6471); PPARδ (agonist GW-50156, antagonist GSK-3787); and PPARγ (agonist rosiglitazone, antagonist GW-9662). Gene expression was assayed through RT-qPCR and RNAseq, and intracellular triacylglycerol (TAG) concentration was measured. PCLS obtained from postpartum cows treated with a PPARγ agonist displayed upregulation of ACADVL and LIPC while those treated with PPARδ agonist had increased expression of LIPC, PPARD, and PDK4. Prepartum PCLS had increased LIPC expression in response to all PPAR agonists. TAG concentration tended to be larger in tissue slices treated with PPARδ agonist compared to CTR. Use of isotype-specific antagonists in PCLS, combined with autologous blood serum, only decreased PDK4 expression. Transcriptome sequencing revealed considerable differences in response to PPAR agonists, with the greatest effects exerted by GW-50156 and Rosiglitazone. Impacted genes were related to pathways involved in lipid metabolism and the immune response. 91 genes were identified as novel putative PPAR targets in the bovine liver by cross-referencing our results with a publicly available dataset of predicted PPAR targets, and confirmed using existing literature. Our results provide important insight on the use of PCLS as a model for assaying PPAR activation in the periparturient dairy cow.